046 Can we predict recovery and re-injury following calf muscle strain injury?. (3rd March 2020) - Green, Brady; Lin, Monica; Schache, Anthony; McClelland, Jodie; Semciw, Adam; Rotstein, Andrew; Cook, Jill; Pizzari, Tania
Abstract : Background: Calf muscle strain injuries (CMSI) are prevalent in sport, but investigations into the variable recovery periods and re-injury are lacking. Objective: To determine whether clinical and MRI findings are predictive of recovery and re-injury following CMSI. Design: Retrospective audit of injury data (2014–2017). Setting: Data from the Soft Tissue injury Registry of the Australian Football League (STRAFL). Patients (or Participants): 149 Australian Football League players. Interventions (or assessment of risk factors): Blinded radiologists assessed MRI characteristics including: the anatomical location of injury, waviness, and severity of aponeurotic disruption (AD): none (0%), mild (<50%), severe (50%-99%), complete (100%). Clinical factors included: age, mechanism, and injury history. Main outcome measurements: The recovery period consisted of four milestones: pain free walking, running at >90% of maximum speed, return to full training, return to play (RTP). Risk factors for re-injury were evaluated for early re-injury (<2 months), and overall (<2 seasons). Multi-variable regression was used to evaluate clinical and MRI predictors of recovery and re-injury. Results: 149 CMSI (114 index, 35 re-injuries) were included: 126 soleus, 17 gastrocnemius, and 6 other. The anatomical location of injury did not impact recovery (all, p>0.05). CMSI with severe AD took on average 11.9 days longer to RTP than injuries with no AD (p=0.003), and the presence of AD (p=0.03) and a running-related mechanism of injury (p=0.01) were the strongest predictors of a longer RTP for soleus injuries. Older age (p=0.001) and a history of a previous ankle injury (p=0.03) were risk factors for early re-injury, while older age (p=0.01) and a history of previous CMSI (p=0.002) were risk factors for re-injury overall. Baseline MRI findings were not associated with re-injury (all, p>0.05). Conclusions: Presence of aponeurotic disruption and a running-related mechanism of injury resulted in longer return to play times for soleus injuries. Only clinical data, not MRI characteristics, were associated with risk of re-injury.